(untitled) (Rome, 2005)
The scientists from the Northwest African region expressed their commitment to conduct their own acoustic surveys. The timeframe of the surveys with R/V Dr Fridtjof Nansen and the support through the Nansen Programme is unknown and high priority must therefore be given to the improvement of scientists skills in acoustic abundance estimation.
Keywords: Fishery resources,Nguồn lợi thủy sản; Africa, Northwest,Châu Phi, Tây Bắc